2010
DOI: 10.3390/molecules15064085
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of a γ-Cyclodextrin-based Formulation of the Anticancer Agent 5,6,11,12,17,18,23,24- Octahydrocyclododeca[1,2-b:4,5-b’:7,8-b’’:10,11-b’’’]tetraindole (CTet)

Abstract: 5,6,11,12,17,18,23,24-octahydrocyclododeca[1,2-b:4,5-b’:7,8-b’’:10,11-b’’’]tetraindole (CTet), an indole-3-carbinol (I3C) metabolite endowed with anticancer properties, is poorly soluble in the solvents most frequently used in biological tests. This study indicates that the use of γ-cyclodextrin (γ-CD) avoids this problem. Formulated with γ-CD CTet is a potent inhibitor of DNA synthesis in both estrogen receptor positive (MCF-7) and estrogen receptor negative (MDA-MB-231) human breast cell lines (IC50 = 1.20 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…It has been previously reported that CTet formulated with γ-CD is able to inhibit proliferation of both MCF-7 and MDA-MB-231 breast cancer cell lines [21]. In this study, we confirm the dose-dependent activity of CTet in both MCF-7 (IC 50 = 1.32 ± 0.03 μM) and MDA-MB-231 (IC 50 = 1.00 ± 0.01 μM).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…It has been previously reported that CTet formulated with γ-CD is able to inhibit proliferation of both MCF-7 and MDA-MB-231 breast cancer cell lines [21]. In this study, we confirm the dose-dependent activity of CTet in both MCF-7 (IC 50 = 1.32 ± 0.03 μM) and MDA-MB-231 (IC 50 = 1.00 ± 0.01 μM).…”
Section: Resultssupporting
confidence: 87%
“…Solvents were Carlo Erba analytic grade. Melting point, high-performance liquid chromatography/mass spectrometry (HPLC/MS), 1 H-NMR, and 13 C-NMR were determined as in [ 21 ]. Purification of the crude material was carried out as in [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested some of our compounds for cytotoxicity, including 1 , 4s , 8 , the reference parent compound DIM, and two other representative 3,3′‐bisindoles: 6,6′‐dibromo,3,3′‐diindolylmethane ( 9 )18 and the natural product 2,2‐bis(3,3′‐indolyl)propionic acid ( 10 ) (Figure 2). 13…”
Section: Resultsmentioning
confidence: 99%
“…Bis(6‐bromo‐1 H ‐indol‐3‐yl)methane (9): H 2 SO 4 (96 %, 2.6 μL) was added to a solution of 6‐bromoindole (195 mg, 0.92 mmol) and aqueous 37 % formaldehyde (37 μL, 0.49 mmol) in CH 3 OH (1 mL). The mixture was stirred at room temperature in the dark for 2 h, and concentrated in the dark to give a crude solid that was purified by flash chromatography (neutral aluminum oxide; cyclohexane/ethyl acetate, 7:3) 18. Yield: 92 mg (49 %); white solid.…”
Section: Methodsmentioning
confidence: 99%